Guanabenz Prevents d-Galactosamine/Lipopolysaccharide-Induced Liver Damage and Mortality - Perego, Jessica; Bourbon, Clarisse; Chasson, Lionel; Laprie, Caroline; Spinelli, Lionel; Camosseto, Voahirana; Gatti, Evelina; Pierre, Philippe (Frontiers in Immunology, 2017)
Multi-organ failure in response to uncontrolled microbial infection is characterized by low blood pressure accompanied by a systemic over-inflammation state, caused by massive pro-inflammatory cytokines release and liver damage. Recently, the integrated stress response (ISR), characterized by eukaryotic translation initiation factor 2α (eIF2α) phosphorylation, was involved with controlling apoptosis in stressed hepatocytes and associated with poor survival to endotoxin challenge. LPS alone is able to induce the ISR in hepatocytes and can trigger massive liver damage along with tumor necrosis factor-alpha (TNF−α) expression. Consequently, drugs interfering with eIF2α phosphorylation may represent potential candidates for the treatment of such pathologies. We therefore used Guanabenz, a small compound with enhancing eIF2α phosphorylation activity to evaluate its effect on bacterial lipopolysaccharides sensing and endotoxemia. Guanabenz is confirmed here to have an anti-inflammatory activity by increasing in vitro IL-10 production by LPS-stimulated dendritic cells. We further show, that in the D-galactosamine (D-galN)/LPS dependent lethality model, intraperitoneal injection of guanabenz efficiently promotes mice survival, by preventing liver damage, increasing IL-10 levels and inhibiting TNF−α production. Guanabenz and its derivatives could therefore represent an interesting pharmacological solution to control systemic inflammation and associated acute liver failure.